Media Sosial dan Masyarakat: Ditinjau Dari Analisis Kultivasi Media - Rahman, Abd; Hilmiyah, Mifda (KOMUNIDA : Media Komunikasi dan Dakwah, 2024)
This study examines in depth the cultivation analysis of media from social media users. Society or social media users, from the perspective of cultivation theory, are always positioned as recipients of all products in the media. Society is considered as passive spectators who only react to what they see and hear in the media. This research focuses on social media because social media is considered the medium closest to society today. Social media is currently the most strategic place to cultivate society, whether it is about fashion, economics, health, social issues, or politics. Therefore, many people use it for promotions on social media. The presence of digital media or social media provides a unique new phenomenon to be researched using cultivation analysis. This research is a literature review that attempts to view, discuss, and actualize Cultivation Theory. The results of this study explain that, according to cultivation theory, messages in the media can influence society.